Malaysian youth ehealth literacy via healthcare websites: a study on factors forming sexual and reproductive health information-seeking intention - George, Andrew Jason; Waheed, Moniza (Universiti Putra Malaysia Press, 2021)
Extensive research has been carried out to study the relationship between Malaysian youth and their perceptions of sexual and reproductive health (SRH); ranging from knowledge and awareness levels to lifestyle choices. However, there is insufficient information on youth e-health literacy levels on the subject matter. Therefore, this study examines the factors that influence youth intention towards using healthcare websites to search for SRH information. This study is guided by the Theory of Reasoned Action (TRA) which suggests that the best indicator of behaviour is intention, which is formed by attitude and subjective norms. Participants for the study were 400 youth (from 18 – 40 years of age) based in the Klang Valley area. Data was collected through a self-administered questionnaire where the research instruments were adopted from the TRA framework, namely: Attitude, Subjective Norms, and Intention. Overall, the findings showed that youth who had positive attitudes and adequate social support/pressure towards using healthcare websites to find SRH information were likely to have a high intention to do so. One crucial finding in the context of this study is how subjective norms are a stronger predictor of SRH information-seeking intention compared to attitude. This finding here can add a new dimension to how the TRA framework is utilised, especially in studies revolving around Asian youth intentions and behaviours. Ministries, NGOs, and private institutions that advocate better SRH practices in Malaysia should leverage the influence of new media to improve health literacy levels among youth.